FORMULATION OF SEREH (Cymbopogon Nardus) AND CITRIC ACID ON THE CHARACTERISTICS OF TELANG FLOWER DRINK (Clitoria Ternatea) AS A READY TO SERVE FUNCTIONAL DRINK - Cahyaning Rini Utami; Putri, Annisa Rachmani (Department of Biology Education, Faculty of Teacher Training and Education, Universitas Wijaya Kusuma Surabaya, 2025)
This research explores the formulation of a ready-to-serve (RTS) beverage utilizing butterfly pea flower (Clitoria ternatea) combined with lemongrass (Cymbopogon nardus) and citric acid to enhance both sensory qualities and antioxidant properties. The study aims to identify the optimal concentrations of lemongrass and citric acid that yield the best sensory attributes and health benefits. A randomized complete block design was employed, featuring two factors: the first factor being the lemongrass concentration (15, 20, and 25 grams) and the second factor the citric acid concentration (0.2, 0.4, and 0.6 grams), resulting in a total of 27 experimental combinations. The researchers utilized two-way ANOVA to analyze the chemical data, followed by Tukey's test to identify significant differences among treatments. Additionally, sensory evaluations were conducted using Friedman's method. The optimal formulation, identified as S3F3, exhibited an antioxidant activity of 5.80 ppm, a pH of 3.5, a color a* value of 3.5, and a color rating of 4.38 (liked). Furthermore, it received a taste score of 4.26 (liked) and an aroma score of 4.26 (liked). These findings indicate that the S3A3 formulation not only aligns with consumer preferences but also provides substantial health benefits, positioning it as a competitive option in the functional beverage market.